The criterion of nationality reform Spanish private international law (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
In the context of the current debate about the recent reform of Spanish Private International Law, this paper attempts to clarify what role nationality should play when determining which law to apply. The advantages and drawbacks of nationality are contrasted with those of domicile and habitual residence. The importance of both the increasing number of foreigners and the position of Spain as a Member State ofthe European Union is also taken into account. The article places special emphasison the recent reform of Article 107 of the Spanish civil code concerning the lawapplied in cases of separation and divorce.
Keywords: Private International Law. Conflict of laws. Nationality. Domicile. Habitual residence. Immigration. European Union